Quality of Chinese government environmental health information disclosure during COVID-19 pandemic: Satisfaction survey on University students - An, Ruikun; Wang, Feng; Hou, Yihan; Hideki, Kitagawa (Frontiers in Public Health, 2022)
Government played a vital role during the COVID-19 pandemic by disclosing related environmental health information to the public. A satisfaction survey is often used to evaluate the public's satisfaction of the government's information disclosure while reflecting problems in the current disclosure system. As University students generally have better cognitive skills, they efficiently received related information during the pandemic, and therefore 717 questionnaires completed by University students were selected for this study. During the pandemic, the quality of the government's environmental health information disclosure system ranked at 13.89, marginally higher than average. Moreover, the timeliness and content adequacy of the disclosure system ranked at a level slightly above average. By adopting Hayes PROCESS Model 4 and 8, this study found that there is a direct impact of environmental health knowledge and environmental health awareness on satisfaction. Furthermore, University students' environmental health knowledge and awareness enhanced satisfaction through the mediating effect of self-reported environmental behavior. Finally, this study attempted to discover the conditions under which environmental health knowledge and awareness would have a greater direct and indirect influence on satisfaction, that is, the reverse moderating effect of household income level. In addition, this paper offers policy recommendations to enhance quality of government environmental health information disclosure system.